Evaluation of Blood Pressure Reduction Response and Responder Characteristics to Fixed‐Dose Combination Treatment of Amlodipine and Losartan: A Post Hoc Analysis of Pooled Clinical Trials. Issue 9 (7th August 2014) - Unniachan, Sreevalsa; Wu, David; Rajagopalan, Srinivasan; Hanson, Mary E.; Fujita, Kenji P.
<x xml:space="preserve">Abstract</x> Data from four clinical trials compared reductions in systolic blood pressure (SBP) and diastolic blood pressure (DBP) among patients treated with amlodipine/losartan 5/50 mg vs 5/100 mg and amlodipine/losartan 5/50 mg vs amlodipine 5 mg and 10 mg. Response rate was assessed as reduction in SBP or DBP (>20/10 mm Hg) and proportion of patients achieving SBP <140 mm Hg or DBP <90 mm Hg. Patients were grouped into quartiles based on baseline SBP and DBP. Mean SBP and DBP were reduced in amlodipine/losartan 5/50 mg (n=182) and amlodipine/losartan 5/100 mg (n=95) users across all baseline quartiles. Patients using amlodipine/losartan 5/50 mg had significantly greater SBP and DBP reductions vs amlodipine 5 mg (P=.001 and P=.02, respectively). Amlodipine/losartan 5/50 mg users had significantly greater SBP reduction vs amlodipine 10 mg (SBP P=.02; DBP P=not significant). The odds of responding to therapy were significantly greater with amlodipine/losartan 5/50 mg vs amlodipine 5 mg (odds ratio, 5.33; 95% confidence interval, 1.42–25.5) and were similar vs amlodipine 10 mg (odds ratio, 0.67; 95% confidence interval, 0.017–9.51). These results support the use of combination therapy early in the treatment of hypertension.